Separating the Grain from the Chaff: Relying on Linguistic Clues to Tell Real News Apart from Fake News: Book Review - Veljanovszki, Dávid (Filológia.hu, 2025)
Grieve, Jack – Woodfield, Helena 2023: The Language of Fake News. Cambridge: Cambridge University Press. Online: https://doi.org/10.1017/9781009349161